Tanggung Jawab Iran Terhadap Penembakan Pesawat Sipil Ukraina Ditinjau Dari Hukum Udara Internasionali - Hasibuan, Nabila; Kusniati, Retno (Uti Possidetis: Journal of International Law, 2020)
Abstract The purpose of this research were to find out and analyze Iran’s responsibility for shooting Ukrainia’s civil aircraft in international air law. The problem that will be discussed is the regulation in international law about the state’s obligation for manage civil aviation safety that trough their territory and Iran’s responsibility for shooting Ukrainia’s civil aircraft in international law. The type that used for this research is normative legal research, the approach in this study is law approach, case approach and historical approach, the sources of legal material used are primary, secondary, and tertiary legal materials. The result of the study show that (1) states whose its airspace passed by civil aircraft must guarantee the aircaft safety in a way regulate the prohibited area if something happen in the territory and the aircraft cant pass through and with a great air navigation civil aircraft safety and security can be guaranteed well. (2) Iran must take full responsibility of this shooting because Iran did not regulate the prohibited area during the conflict. In the future, it is necessary to emphasize the state’s responbility for the route for internationl civil aviation and cooperate with other parties so that safety and security on international aviation can be achhieved.